The longitudinal association between the context of physical activity and mental health in early adulthood. (March 2018) - Doré, Isabelle; O'Loughlin, Jennifer L.; Schnitzer, Mireille E.; Datta, Geetanjali D.; Fournier, Louise
Abstract: This study examined the associations between the context in which physical activity (PA) is undertaken (team sports, informal group, individual PA), and each of positive mental health, anxiety symptoms and depressive symptoms. It also investigated whether social connectedness or PA volume mediate these associations. A total of 460 students (62.4% female; mean age at baseline = 18.5, SD 2.6) completed questionnaires at baseline and at follow-up 6 months later. Multivariate linear regression was used to model the associations between PA context at baseline and each outcome at follow-up controlling for sex, age, perceived socioeconomic status and baseline values of the outcome. Mediation analyses used causal inference methods to estimate the controlled direct effect (CDE), natural direct (NDE) and indirect effects (NIE) of social connectedness and PA volume. Relative to individual PA, informal group PA and team sports were positively associated with positive mental health ( β ˆ (95% CI) = 2.24 (0.01, 4.46) and 3.39 (0.74, 5.59) respectively), and inversely associated with depressive symptoms (−0.65 (−1.29, −0.01) and −0.76 (−1.43, −0.09), respectively). A significant CDE was observed for PA volume on the association between team sports and positive mental health ( β ˆ (95% CI) = 2.72 (0.03, 5.34)), suggesting that there is no benefit from increasing PA volume and that it is specifically the context of team sports that provides the benefit on positive mental health. Efforts to promote mental health and prevent depressive symptoms may benefit from intervention promoting PA in informal group and team sport settings. Highlights: Group PA and team sports are associated with increased mental health. Group PA and team sports are associated with decreased depressive symptoms. Social connectedness and PA volume significantly different across PA contexts. Benefit of participation in team sports on mental health is not affected by the volume.